2018
DOI: 10.1016/j.rbmo.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Shared motherhood IVF: high delivery rates in a large study of treatments for lesbian couples using partner-donated eggs

Abstract: Shared motherhood IVF treatment is becoming increasingly accepted among assisted reproductive techique practitioners and patients in Europe, although data on its overall efficiency remain scarce. This 6-year retrospective study from a single, private, UK HFEA-regulated centre included consecutive lesbian couples (n = 121) undergoing shared motherhood IVF treatment (141 cycles). Recipients were more parous and had undergone more previous intrauterine insemination and IVF treatments than donor partners, who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 12 publications
1
36
2
Order By: Relevance
“…The purpose was to examine the trend of development in this area after legalization of the registered partnership of the some sex couples in 2006 and the adoption of antidiscrimination laws in 2009. 15 , 27 , 28 All study procedures were approved by the Ethical Review Board of Centrum MEDIOL.…”
Section: Methods and Samplementioning
confidence: 99%
“…The purpose was to examine the trend of development in this area after legalization of the registered partnership of the some sex couples in 2006 and the adoption of antidiscrimination laws in 2009. 15 , 27 , 28 All study procedures were approved by the Ethical Review Board of Centrum MEDIOL.…”
Section: Methods and Samplementioning
confidence: 99%
“…We primarily compared our ROPA results with previously published data from the UK, Spain, and USA. [6][7][8] Baseline characteristics of participants were quite similar across all four studies. The mean age and age range of the oocyte provider was 35.1 (25-42) in Marina et al, 7 38.1 (34-43) in Yeshua et al, 8 32.4 (20-41) in Bodri et al, 6 and 34.2 (25-45) in our study.…”
Section: Discussionmentioning
confidence: 87%
“…[6][7][8] Baseline characteristics of participants were quite similar across all four studies. The mean age and age range of the oocyte provider was 35.1 (25-42) in Marina et al, 7 38.1 (34-43) in Yeshua et al, 8 32.4 (20-41) in Bodri et al, 6 and 34.2 (25-45) in our study. Notably, we report a higher live birth rate after the first ET (57.1%) compared with the first ROPA study, 7 as well as the study of Yeshua et al 8 Marina et al 7 reported 1 live birth out of 13 ETs performed, but 3 pregnancies were still ongoing at the time of publication; hence the live birth rate was expected to be between 7.7% and 30.8%.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations